2007
DOI: 10.1634/stemcells.2007-0267
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Cooperate with Bone Marrow Cells in Therapy of Diabetes

Abstract: Several recent studies have suggested that the adult bone marrow harbors cells that can influence ␤-cell regeneration in diabetic animals. Other reports, however, have contradicted these findings. To address this issue, we used an animal model of type 1 diabetes in which the disease was induced with streptozotocin in mice. Freshly prepared sexmismatched bone marrow cells (BMCs) and syngeneic or allogeneic mesenchymal stem cells (MSCs) were concomitantly administrated into sublethally irradiated diabetic mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(182 citation statements)
references
References 58 publications
5
167
2
8
Order By: Relevance
“…This may be due to attraction of stem cells by the diabetic pancreas. This finding was explained by Körbling et al (27) (34) reported that administration of BMCs with MSCs normalized the blood glucose level and serum insulin levels in STZ-induced diabetic mice. This allowed regeneration of recipient-derived pancreatic insulin-secreting cells.…”
Section: -Fold (20)mentioning
confidence: 76%
“…This may be due to attraction of stem cells by the diabetic pancreas. This finding was explained by Körbling et al (27) (34) reported that administration of BMCs with MSCs normalized the blood glucose level and serum insulin levels in STZ-induced diabetic mice. This allowed regeneration of recipient-derived pancreatic insulin-secreting cells.…”
Section: -Fold (20)mentioning
confidence: 76%
“…One possible explanation for this efficacy could be related to the regeneration of pancreatic islets by MSCs; however, we considered this hypothesis unlikely since protection was obtained during the early inflammatory phase of the disease. Moreover, Urban et al [31] have recently reported in a streptozotocin-induced mouse model of diabetes that MSCs cannot induce pancreas regeneration by themselves, as they require co-injection of bone marrow stem cells. In addition, clinical efficacy in our model was correlated with greatly decreased insulitis scores, further suggesting immune-mediated, rather than regenerative, mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…75 Similarly, co-infusion of MSCs and BM cells, following sublethal irradiation, inhibited the proliferation of b-cell-specific T cells isolated from the pancreas of diabetic mice and restored insulin and glucose levels through the induction of regenerated recipient-derived pancreatic b-cells in the absence of transdifferentiation. 76 The immunosuppressive effect of MSCs on T cells was also exploited in a multi-organ autoimmunity mouse model in which MSCs homed in the mesenteric lymph nodes, significantly improving autoimmune enteropathy. 77 These results confirm the therapeutic plasticity of MSCs owing to their capacity of modulating systemic autoimmunity and protecting target tissues.…”
Section: Animal Models Of Autoimmunitymentioning
confidence: 99%